Hundred Fifty Years of Herbarium Collections Provide a Reliable Resource of Volatile Terpenoid Profiles Showing Strong Species Effect in Four Medicinal Species of Salvia Across the Mediterranean - Foutami, Isa Jafari; Mariager, Trine; Rinnan, Riikka; Barnes, Christopher James; Rønsted, Nina (Frontiers in Plant Science, 2018)
Herbarium samples are increasingly being recognised for their potential in answering a wide range of research questions. However, the suitability of herbarium samples for chemical analysis is largely unexplored as they are thought to be too degraded. The aim of this study was to explore terpenoid profiles across time and geographic space for four medicinal species of Salvia across the Mediterranean to assess the suitability of using herbarium specimens in chemical analyses. Herbarium samples of Salvia aethiopis, S. multicaulis, S. officinalis and S. sclarea collected over 150 years across the Mediterranean were compared to modern samples using both targeted and untargeted gas chromatography-mass spectrometry analysis of terpene profiles. There was no effect of collection year on chemical composition, although the total concentration of the 20 assessed standards and two individual standards significantly decreased over time. Instead, chemical profiles were defined by species, with strong species effects identified on both the targeted and untargeted chemical composition. Geographic variation was a factor in regulating the untargeted chemical compositions, suggesting some underlying environmental effects. However, there was no effect of sample altitude on either the targeted or untargeted chemical compositions. Chemical composition of four Salvia species are predominantly defined by species, and there was a substantially smaller effect of year of sampling. Given these results herbarium collections may well represent a considerably underused resource for chemical analyses that can benefit biodiversity and other studies.